Literary Autobiography and Subject Formation: A Comparative Study of Mona Enamouri's a Chat Upon Thames and Elif Shafak's Black Milk - Alakhdar, Ghada Mohamad Ali Hassan (Wadī Al-Nīl Lil Dirāsāt wa Al-Buẖūṯ Al-Insāniyyaẗ wa Al-Iğtimāʿiyyaẗ wa Al-Tarbawiyyat, 2020)
The two novels, Mona Enamouri's A Chat Upon Thames (2014) and Elif Shafak's Black Milk (2007), are autobiographical writings that depict the process of self-representation revealing a postmodern feminist interest in subject formation. Enamouri, on one hand, reflects on the self between places and voices revealing a construction of awareness and self-definition in reaction to external experiences. Shafak, on the other, interweaves a number of questions on female body and identity within the contextual struggle of patriarchical society and intrinsic emotional-personality struggles. Pregnancy and post-partum depression are discussed in line with questions of what it means to have a family, construct a book and determine self-worth. Negotiating a range of feminist thematic preoccupations with voice, spaces, and body the two novels unravel the critical function of feminist autobiographies in constructing the self from "discordant" voices through a dynamic process of self-representation through creation.